Is There a Need for a Fourth EU Pillar? - EKENGREN, MAGNUS (Cooperation and conflict, 2002)
Examines the success of the 2001 Swedish Presidency of the European Union (EU) Council of Ministers in the area of employment & social policy cooperation. A tension is revealed between the Swedish presidency's goals of deepening the EU in terms of creating new areas of cooperation & actually implementing institutional adaptation to such changes via an "open method of coordination" (OMC). To the goals expressed by the 2000 European Council in Lisbon, Portugal, the Swedes added four new foci: demographic challenges, biotechnology, sustainable development, & environmentally propelled growth. Timetables were established for discussing pensions, health care, & elder care, as well as services for the disabled & children. New employment objectives were set, & standards for evaluating quality of work created. The goal of setting deadlines for the deregulation of the energy (gas & electricity) market was less successful. Several problems with the OMC are identified, highlighting relations between the EU & its institutions & member states. Dimensions of the current balance of power between three pillars -- the EU, the Council, & the European Commission -- are described, & possibilities for the creation of a "fourth pillar" to further elaborate pragmatic sector-specific coordination -- "active subsidiarity" -- are explored. 8 References. K. Hyatt Stewart